Diagnostic and treatment behaviour in children with chronic respiratory symptoms: relationship with socioeconomic factors. Issue 8 (1st August 2002) - Ng Man Kwong, G; Das, C; Proctor, A R; Whyte, M K B; Primhak, R A
Abstract : Background: The prevalence and severity of asthma is believed to increase with increasing socioeconomic deprivation. The relationship between asthma diagnosis, symptoms, diagnostic accuracy, and socioeconomic deprivation as determined by Townsend scores was determined in Sheffield schoolchildren. Methods: All 6021 schoolchildren aged 8–9 years in one school year in Sheffield were given a parent respondent survey based on International Survey of Asthma and Allergies in Childhood (ISAAC) questions. Results: 5011/6021 (83.2%) questionnaires were returned. Postcode data were available in 4131 replies (82.4%) and were used to assign a composite deprivation score (Townsend score). Scores were divided into five quintiles, with group 1 being least and group 5 being most deprived. A positive trend was observed from group 1 to group 5 for the prevalence of wheeze in the previous 12 months, wheeze attacks ≥4/year, nocturnal wheeze and cough (all p<0.001), cough and/or wheeze "most times" with exertion (p<0.03), current asthma (p<0.001), and significant asthma symptoms (p<0.001). No significant trend was observed for lifetime wheeze or attacks of speech limiting wheeze. There were no significant trends in the prevalence of current asthmatic children without significant symptoms (overdiagnosis) or children with significant asthma symptoms but no current asthma diagnosis (underdiagnosis) across the social groups. There was a significant negative trend in the ratio of asthma medication to asthma diagnosis from least to most deprived groups (p<0.001). Conclusions: Asthma morbidity and severity increase according to the level of socioeconomic deprivation. This may be due to differences in environment, asthma management, and/or symptom reporting. Diagnostic accuracy does not vary significantly across deprivation groups but children living in areas of least deprivation and taking asthma medication are less likely to be labelled as having asthma, suggesting diagnostic labelling bias.